Mutation in flrA and mshA Genes of Vibrio cholerae Inversely Involved in vps-Independent Biofilm Driving Bacterium Toward Nutrients in Lake Water - Sinha-Ray, Shrestha; Ali, Afsar (Frontiers in Microbiology, 2017)
Many bacterial pathogens promote biofilms that confer resistance against stressful survival conditions. Likewise Vibrio cholerae O1, the causative agent of cholera, and ubiquitous in aquatic environments, produces vps-dependent biofilm conferring resistance to environmental stressors and predators. Here we show that a 49-bp deletion mutation in the flrA gene of V. cholerae N16961S strain resulted in promotion of vps-independent biofilm in filter sterilized lake water (FSLW), but not in nutrient-rich L-broth. Complementation of flrA mutant with the wild-type flrA gene inhibited vps-independent biofilm formation. Our data demonstrate that mutation in the flrA gene positively contributed to vps-independent biofilm production in FSLW. Furthermore, inactivation of mshA gene, encoding the main pilin of mannose sensitive hemagglutinin (MSHA pilus) in the background of a ∆flrA mutant, inhibited vps-independent biofilm formation. Complementation of ∆flrA∆mshA double mutant with wild-type mshA gene restored biofilm formation, suggesting that mshA mutation inhibited ∆flrA-driven biofilm. Taken together, our data suggest that V. cholerae flrA and mshA act inversely in promoting vps-independent biofilm formation in FSLW. Using a standard chemotactic assay, we demonstrated that vps-independent biofilm of V. cholerae, in contrast to vps-dependent biofilm, promoted bacterial movement toward chitin and phosphate in FSLW. A ∆flrA∆mshA double mutant inhibited the bacterium from moving toward nutrients; this phenomenon was reversed with reverted mutants (complemented with wild-type mshA gene). Movement to nutrients was blocked by mutation in a key chemotaxis gene, cheY-3, although, cheY-3 had no effect on vps-independent biofilm. We propose that in fresh water reservoirs, V. cholerae, on repression of flagella, enhances vps-independent biofilm that aids the bacterium in acquiring nutrients, including chitin and phosphate; by doing so, the microorganism enhances its ability to persist under nutrient-limited conditions.